Reliability and Validity of the Chen Depression Scale: A Preliminary Study - Yi-Lung Chen; Sophie Hsin-Yi Liang; Mong-Liang Lu; Vincent Chin-Hung Chen (Taiwanese Journal of Psychiatry, 2024)
Objective: Major depressive disorder (MDD) is an important psychiatric illness worldwide. We developed the Chen Depression Scale (CDS) based on the criteria of the Diagnostic and Statistical Manual for Mental Disorders, Fifth Edition. In this study, we intended to evaluate the psychometric properties of the CDS.